PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP HASIL BELAJAR SISWA SUBTEMA 4 CUACA, MUSIM, DAN IKLIM KELAS III SD SWASTA HKBP TOMUAN PEMATANGSIANTAR - Wina Sirait; Melvin M. Simanjuntak; Eva Pasaribu (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This resea.rch a.ims to determine the effect of the Project-Ba.sed Lea.rning Model on the lea.rning outcomes of cla.ss III students on wea.ther, sea.sons a.nd clima.te a.t HKBP Tomua.n Pema.ta.ngsia.nta.r Priva.te Elementa.ry School. The type of resea.rch used is qua.ntita.tive resea.rch with experimenta.l methods. The resea.rch popula.tion wa.s in cla.ss III of HKBP Tomua.n Pema.ta.ngsia.nta.r Priva.te Elementa.ry School Jl. Sia.ta.s Ba.rita. No. 38 which is loca.ted in Ea.st Sia.nta.r District. The sa.mple in this resea.rch wa.s ta.ken from one cla.ss which wa.s used a.s a. One Group cla.ss so tha.t the sa.mples in this resea.rch were a.ll cla.ss III students a.t HKBP Tomua.n Pema.ta.ngsia.nta.r Priva.te Elementa.ry School, tota.ling 21 students. The da.ta. collection technique in this resea.rch uses a. test in the form of multiple choice questions which ha.s four choices, na.mely a. b c a.nd d with a. tota.l of 20 questions. The resea.rch results obta.ined were tha.t there wa.s a.n increa.se in student lea.rning outcomes, na.mely with a.n a.vera.ge posttest of 85 while the pretest wa.s 58.09. The results of this resea.rch a.re strengthened by the results of the N-Ga.in Test which shows tha.t the a.vera.ge va.lue of the N-Ga.in Score is 82.65 or is ca.tegorized a.s high, so it ca.n be concluded tha.t va.ria.ble X (Project-ba.sed lea.rning model) ha.s a. significa.nt effect on va.ria.ble Y (student lea.rning outcomes ).